Effects of the IL-23–IL-17 pathway on bone in spondyloarthritis. Issue 11 (November 2018) - Gravallese, Ellen; Schett, Georg
Abstract Over the past several years, a pathophysiological role for the IL-23–IL-17 pathway in human disease has been defined. A subset of rheumatic diseases, including psoriatic arthritis (PsA) and ankylosing spondylitis (AS), are now acknowledged to be triggered by dysregulated IL-23–IL-17 pathway activation. Genetic evidence links the IL-23–IL-17 pathway to inflammation in these rheumatic diseases, and mechanistic data from mice support a functional role for IL-23–IL-17 pathway activation in the development of enthesitis and in entheseal bone formation. Furthermore, analysis of human tissue samples, as well as data from clinical trials, also supports a role for activation of the IL-23–IL-17 pathway in these diseases. The unique bone phenotype that occurs in PsA and AS is a surprising coexistence of both systemic bone loss and periosteal and entheseal bone formation and is likely to be the result of the actions of IL-23 and/or IL-17 on bone. However, the effects of these cytokines on bone cells are complex, and controversy remains regarding their exact roles in the specific bone microenvironments relevant to PsA and AS. The IL-23–IL-17 signalling pathway has paradoxical effects on bone remodelling in psoriatic arthritis and ankylosing spondylitis. In this Review, Gravallese and Schett examine the evidence for and outline the reasons behind this paradox. Key points IL-23 is produced by activated myeloid cells, whereas IL-17 is predominantly produced by T cells and innate lymphoid cells. Several lines of evidence support a role for the IL-23–IL-17 pathway in the pathogenesis of psoriatic arthritis (PsA) and ankylosing spondylitis (AS). Bone changes that occur in PsA and AS include systemic bone loss, articular erosions and entheseal bone formation and reflect the combined effects of IL-23 and IL-17. IL-17A promotes osteoclastogenesis directly, as well as indirectly, through the production or induction of receptor-activator of nuclear factor-κB ligand (RANKL) expression, whereas the effects of IL-23 on osteoclasts are pleotropic. IL-17A exhibits differential effects on the maturation of osteoblast precursor cells to osteoblasts depending upon the stage of differentiation of the cellular precursor. IL-17A blockade inhibits articular bone erosion and might also retard systemic bone loss in PsA and AS and enthesophyte formation in PsA.